The Influence of Fiscal and Monetary Policy on Indonesia's Economic Growth - Ririn Mardhani Syakur; Indraswati Tri Abdi Reviane; Abdul Hamid Paddu (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
The government has two policies in promoting economic growth, namely monetary policy, and fiscal policy. The purpose of this research is to see the extent to which the effectiveness of fiscal and monetary policies in influencing economic growth in Indonesia, as well as to see the effect of unemployment and investment in mediating the relationship between the dependent variables (taxes, government spending, credit interest rates, and the money supply) on economic growth. in Indonesia for the period 2000-2019. The research approach uses a quantitative approach which is carried out in the form of path analysis with time-series data in the annual period, namely from 2000 to 2019. The data used is secondary data obtained from various sites of the Indonesian Central Statistics Agency, Bank Indonesia, World Bank, etc. The results of this study are direct taxes and government spending have a positive effect on economic growth, but credit interest rates and the money supply have a negative effect. While the indirect effect of taxes and government spending on economic growth through unemployment and investment has a negative effect, interest rates and the money supply have a positive effect.